Clinical and endoscopic profile of patients with Mallory- Weiss tears - Bhattarai, Subash; Dewan, Khus Raj; Shrestha, Gaurav; Patowary, Bhanumati Saikia (Asian Journal of Medical Sciences, 2017)
Background: Mallory-Weiss tear is mainly located across the gastro-esophageal mucosal junction and presents with upper gastro-intestinal bleed of less severity. Haemorrhage frequently ceases spontaneously.Aims and Objective: This study was undertaken to establish the incidence, clinical and endoscopic profile of patients with Mallory- Weiss tear.Materials and Methods: Six hundred patients presenting with acute upper gastro-intestinal (UGI) bleed were included in the study. All patients underwent UGI endoscopy after achieving haemodynamic stability, usually within 24 hours. Cases with Mallory Weiss tear were identified and their clinical presentation, endoscopic findings, outcomes during hospitalization including rebleeding and mortality were studied.Results: Twenty eight (4.6%) patients out of six hundred acute upper gastro-intestinal bleed were diagnosed with Mallory-Weiss tear. Fourteen (50%) patients gave history of prior vomiting or preceeding retching. Only two patients (7.1%) presented with shock. The most common co-morbid condition was excessive alcohol consumption. Eighteen (64.3%) patients had no active bleeding during UGI endoscopy. All patients except four presented with a single tear with mean length of two cms. Blood transfusion was needed in eight (28.6%) patients only. Only one patient had re-bleeding. Average hospital admission was three days. No mortality was recorded in 7 days and 28 days of follow ups.Conclusions: Mallory-Weiss tear is not an uncommon cause of UGI bleeding nowadays and its incidence is rising every year. Hemorrhage frequently ceases spontaneously and conservative management is sufficient in many instances. When endoscopic findings reveal active haemorrhage, various endoscopic hemostatic techniques can be used.Asian Journal of Medical Sciences Vol.8(6) 2017 19-23